Fracture risk in Korean postmenopausal women: The influence of BMI, age, and bone density - Shin, Junghwa; Kim, Kwang Yoon; Park, Joo-hyun; Lee, Sangmi; Noh, O Kyu; Choi, Yong Jun; Chung, Yoon-Sok; Kim, Bom-Taeck (Osteoporosis and Sarcopenia, 2025)
Fracture risk in postmenopausal women is influenced by bone mineral density (BMD), age, and body mass index (BMI). However, fracture prevention strategies primarily focus on low BMD, often overlooking other key factors. This retrospective cohort study analyzed 18,151 Korean postmenopausal women aged 50 or older who underwent dual-energy X-ray absorptiometry (DXA) at Ajou University Hospital from years of 2006–2014. Fracture risk was assessed using multivariable Cox proportional hazard models, adjusted for BMI, BMD, and age. The median age of the cohort was 59.1 years, and the overall fracture incidence was 2.3 per 1,000 person-years. Fracture risk significantly increased with age, with hazard ratios (HRs) of 1.36 (95% CI: 1.08–1.70) for women aged 60–69 and 2.10% (95% CI: 1.62–2.73) for those aged 70 or older, compared to the reference group (50–59 years). Underweight women exhibited the highest fracture cumulative incidence (3.3%), though their risk increase was not statistically significant. Overweight and obese women demonstrated higher BMD but did not show significant fracture risk reductions. These findings highlight age as a dominant predictor of fracture risk, while BMI plays a complex, less pronounced role. The discrepancy between osteoporosis prevalence and actual fracture risk, particularly in obese elderly women, suggests limitations in BMD-focused assessments. Simple, measurable parameters like age and BMI should complement BMD in fracture risk evaluation to better target high-risk populations and enhance preventive strategies in clinical practice.